Increased levels of VEGF-C and macrophage infiltration in lipedema patients without changes in lymphatic vascular morphology - Felmerer G; Stylianaki A; Hollmen M; Strobel P; Stepniewski A; Wang AN; Frueh FS; Kim BS; Giovanoli P; Lindenblatt N; Gousopoulos E (NATURE PUBLISHING GROUP, 2022)
Lipedema is a chronic adipose tissue disorder characterized by the disproportional subcutaneous deposition of fat and is commonly misdiagnosed as lymphedema or obesity. The molecular determinants of the lipedema remain largely unknown and only speculations exist regarding the lymphatic system involvement. The aim of the present study is to characterize the lymphatic vascular involvement in established lipedema. The histological and molecular characterization was conducted on anatomically-matched skin and fat biopsies as well as serum samples from eleven lipedema and ten BMI-matched healthy patients. Increased systemic levels of vascular endothelial growth factor (VEGF)-C (P=0.02) were identified in the serum of lipedema patients. Surprisingly, despite the increased VEGF-C levels no morphological changes of the lymphatic vessels were observed. Importantly, expression analysis of lymphatic and blood vessel-related genes revealed a marked downregulation of Tie2 (P<0.0001) and FLT4 (VEGFR-3) (P=0.02) consistent with an increased macrophage infiltration (P=0.009), without changes in the expression of other lymphatic markers. Interestingly, a distinct local cytokine milieu, with decreased VEGF-A (P=0.04) and VEGF-D (P=0.02) expression was identified. No apparent lymphatic anomaly underlies lipedema, providing evidence for the different disease nature in comparison to lymphedema. The changes in the lymphatic-related cytokine milieu might be related to a modified vascular permeability developed secondarily to lipedema progression.